PENERAPAN MODEL COOPERATIVE TIPE MAKE A MATCH PADA MATERI ORGAN GERAK HEWAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V MIN 17 PIDIE - Junaidah (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2019)
The aim of the research is to identify whether by using the cooperative make a match type model can increase the students learning outcomes. This Classroom Action Research consists of three cycles with some stages i.e. planning, acting, observing and reflecting. The subject of the research was the fifth grade students who totally 34 students, in which consisted of 22 females and 12 males. The result of the research indicated that the students obtained the average and classical achievements respectively at cycle I are 65 and 41.18%. Cycle II are 75.29 and 70.58%. And cycle III are 92.35 and 100%. So the finding shows if by using the model it can increase the students’ learning outcomes.